If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.25(4x + -4) = -2t + 10x + 12 Reorder the terms: 2.25(-4 + 4x) = -2t + 10x + 12 (-4 * 2.25 + 4x * 2.25) = -2t + 10x + 12 (-9 + 9x) = -2t + 10x + 12 Reorder the terms: -9 + 9x = 12 + -2t + 10x Solving -9 + 9x = 12 + -2t + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -9 + 9x + -10x = 12 + -2t + 10x + -10x Combine like terms: 9x + -10x = -1x -9 + -1x = 12 + -2t + 10x + -10x Combine like terms: 10x + -10x = 0 -9 + -1x = 12 + -2t + 0 -9 + -1x = 12 + -2t Add '9' to each side of the equation. -9 + 9 + -1x = 12 + 9 + -2t Combine like terms: -9 + 9 = 0 0 + -1x = 12 + 9 + -2t -1x = 12 + 9 + -2t Combine like terms: 12 + 9 = 21 -1x = 21 + -2t Divide each side by '-1'. x = -21 + 2t Simplifying x = -21 + 2t
| 3+k/3=3 | | 2(s+2)=6 | | 3.5=130+10x | | (-4)(p+8)=12 | | 150m-100m+39000=40000-150m | | 22+2z=37+6*z | | 12w-19w-1=13 | | w(w-13)=0 | | -x+2(4-x)=-4 | | Sin(x)=-1 | | 6y=-120 | | 6x=32 | | 16=p-(-3) | | 10m+8b-12=0 | | -15+7x=-79 | | (x+3)+(y-5)=36 | | -25(d+2)= | | 14x+9y=310 | | 16.4(2x+11)=6x+33 | | 2990=4*660+6y | | 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x | | Y-2=-1(x+7) | | 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y | | x+y-8x+6y-125=0 | | X-15=-50 |